The Relationship between Peer Relationship Quality and Anxiety among Late Adolescents in Surakarta City - Zalfaa Alya Fauzia; Malida Fatimah (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aimed to examine the relationship between peer relationship quality and anxiety among late adolescents in Surakarta City. This study employed a quantitative approach with a correlational design. The research subjects comprised 170 late adolescents aged 18–21 years who resided or were pursuing education in Surakarta City, selected using an accidental sampling technique. Data were collected using the Peer Relationship Quality Scale, developed based on the Friendship Quality Scale (FQS), and the Anxiety Scale, adapted from the State-Trait Anxiety Inventory (STAI). Data were analyzed using Pearson Product Moment correlation following the fulfillment of normality and linearity assumption tests. The results revealed a significant negative relationship between peer relationship quality and anxiety among late adolescents (r = −0.271; p = 0.000). These findings indicate that higher peer relationship quality is associated with lower levels of anxiety among late adolescents, whereas lower peer relationship quality is associated with higher levels of anxiety. The findings of this study suggest that positive peer relationships function as a protective factor in safeguarding the mental health of late adolescents. Accordingly, strengthening the quality of social relationships among peers may serve as an effective strategy for preventing and addressing anxiety among adolescents.